Finance and development in Africa - Menjah, Kojo; Abor, Joshua (Emerald, 2012)
The objective of "Research in Accounting in Emerging Economies" is to raise the level of interest in the specific problems of accounting in emerging economies; and increase awareness of real issues, so that accounting in these countries will not just be seen as a matter of copying what is done in the industrialized countries. "RAEE" is intended to provide an authoritative overview of accounting research and progress in emerging economies.
Keywords: Business & Economics -- Accounting -- General.; Accounting.; Finance, Public -- Africa.; Africa -- Economic conditions.; elektronické knihy; electronic books